6-mm-long implants loaded with fiber-reinforced composite resin-bonded fixed prostheses (FRCRBFDPs). A 5-year prospective study - Rossi, Fabio; Lang, Niklaus P.; Ricci, Emanuele; Ferraioli, Lorenzo; Marchetti, Claudio; Botticelli, Daniele (Wiley-Blackwell, 2017)
AimTo evaluate the clinical and radiographic outcomes and the survival rates of fiber-reinforced composite resin-bonded fixed prostheses (FRCRBFDPs) placed in the posterior area supported by two short (6mm) implants. Materials and MethodsTwenty consecutive patients received 40 SLActive 6-mm-long implants with a diameter of 4.1mm (n=29) or 4.8mm (n=11). Insertion torques and RFA (Resonance Frequency Analysis) were measured at implant installation. The prosthetic rehabilitation was performed after 8weeks from insertion with a screw-retained two- or three-unit fixed dental prosthesis fabricated of FRCRBFDPs. Implant survival rates and marginal bone levels were evaluated at various time intervals until 5years after loading. ResultsTwo of 20 patients lost four implants supporting two FRCRBFDPs between the second and the third year of follow-up (cumulative survival rate: 90% after 5years). Four patients suffered a fracture of the prosthetic reconstruction, and the success rate of the rehabilitation was 70% after 5years. A mean marginal bone loss of 0.300.34mm was found after 5years of function at the remaining implants. ConclusionThe survival of short implants was 90% owing to two bridges losses in the maxilla. However, the success rate of FRCRBFDPs over 5years was only at 70%.
Keywords: dental implants; early loading; fiber-reinforced resin-bonded; fixed partial dentures; implant length; prospective study; short implants